Dampak Post-Truth di Media Sosial - Nuhdi Futuhal Arifin; A. Jauhar Fuad (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2020)
This article reviews the background of the emergence of Post-truth and the impact of Post-truth. This lecture uses literature review by examining various sources of reading in mass media and social media. The results of this paper explain that in Indonesia Post-truth auctioning and post-election 2019 is rife on social media. Post-truth on social media does not stop there but continues to roll on various problems that exist in this country. Starting is an ethnicity, religion, and race. Hoaxes and hate speech using social media platforms as a means of spreading are not trivial matters, because the series of attacks may continue to surge. The pressure from social media often forms wild and uncontrollable opinions, which are hoped to be exploited by some groups for certain interests.